Evolution and codon usage bias of mitochondrial and nuclear genomes in Aspergillus section Flavi - Miya Hugaboom; Elizabeth Anne Hatmaker; Abigail L LaBella; Antonis Rokas (G3: Genes, Genomes, Genetics, 2022)

(untitled)
AbstractThe fungal genus AspergillusFlaviFlavi